PENGEMBANGAN LEMBAR KERJA SISWA (LKS) DENGAN TAMPILAN MAJALAH PADA MATERI ZAT ADITIF DAN ZAT ADIKTIF UNTUK SISWA SMP - Rahmadani, Dessy Mulya (Pendidikan Biologi, 2014)
Based on writer observation result to SMPN 23 Padang can be gotten information that one of material which is used in learning process like LKS. LKS which is used is not interested especially in additive substance and addictive substance. The view of LKS is so simple, picture illustration which is available in LKS is lack of communicative and without variation color just only black and white cause students are not interested and lack of spirit in doing LKS. Related on it, we need to develop LKS by magazine view. This research purpose to produce LKS by magazine view in additive substance and addictive substance for SMP and know validity and practicality. This research is developed research which is used 4-D model, they are define (define), design (design), develop(develop), disseminate. the define level is consist of front analysis, student analysis, and task analysis. In design level, itâs done material design like LKS with magazine view in additive substance and addictive substance material, then develop level is done validity test by validation which is consist of 2 lectures form STKIP PGRI West Sumatera and 2 teachers from SMPN 23 Padang. Practicality test by 2 teachers and 25 students in class IX SMPN 23 Padang. The disseminate level , itâs not done because itâs only until develop. The data research is premier data and validity is analyzed and itâs practicality which is gotten from questionnaire validity and practicality. The result of LKS validity by magazine view from validation show that LKS by magazine view like this is in valid criteria. Itâs 87,91% is shown from suitable material, language and view. The result of LKS practicality by magazine view by the teacher and student show that LKS by magazine view in very practicality criteria 96,38% and 88,04% is shown from the easiness in use, advantage and time efficiency. It can be concluded that LKS by magazine view in additive substance and addictive substance which is produced has completed valid criteria and very practice.